(untitled) (The Pakistan Development Review, 1981)
Data from Pakistan’s population planning programme, the National Impact Survey (968) and the Pakistan Fertility Survey (1975) are analysed to estimate the number of ’births averted’ in Pakistan by various contraceptives. Limitations of the population planning programme statistics for determining the impact of the programme on fertility rates arc pointed out.